Positional differences of axon growth rates between sensory neurons encoded by runx3 - Lallemend, Francois (Nature Publishing Group, 2012)
The formation of functional connectivity in the nervous system is governed by axon guidance that instructs nerve growth and branching during development, implying a similarity between neuronal subtypes in terms of nerve extension. We demonstrate the molecular mechanism of another layer of complexity in vertebrates by defining a transcriptional program underlying growth differences between positionally different neurons. The rate of axon extension of the early subset of embryonic dorsal root ganglion sensory neurons is encoded in neurons at different axial levels. This code is determined by a segmental pattern of axial levels of Runx family transcription factor Runx3. Runx3 in turn determines transcription levels of genes encoding cytoskeletal proteins involved in axon extension, including Rock1 and Rock2 which have ongoing activities determining axon growth in early sensory neurons and blocking Rock activity reverses axon extension deficits of Runx3(−/−) neurons. Thus, Runx3 acts to regulate positional differences in axon extension properties apparently without affecting nerve guidance and branching, a principle that could be relevant to other parts of the nervous system.